Combined therapies versus monotherapies for the first variceal bleeding in patients with high‐risk varices: A meta‐analysis of randomized controlled trials. Issue 3 (March 2014) - Bai, Ming; Qi, Xingshun; Yang, Man; Han, Guohong; Fan, Daiming
Abstract Background and Aim The effect of combined therapies (among non‐selected beta‐blockers [NSBB], endoscopic therapy, and other treatments) on the first variceal bleeding has been evaluated in several randomized controlled trials previously, and the results were controversial. We performed this meta‐analysis to assess the effect of combined therapies in patients with high‐risk varices without previous variceal bleeding. Methods The Cochrane Library, The Cochrane Hepato‐Biliary Group Controlled Trials Register, MEDLINE, and EMBASE were searched for eligible trials. Manual searches were also performed for additional studies. Upper gastrointestinal bleeding, variceal bleeding, mortality, and adverse events were evaluated as end‐points by meta‐analysis. Results Twelve randomized controlled trials with 1571 patients were included. Compared with the NSBB (propranolol or nadolol) or endoscopic therapy alone, all of the combined therapies did not demonstrate significant improvements in variceal bleeding, total upper gastrointestinal bleeding, and mortality. Only the combinations of isosorbide‐mononitrate or spironolactone with NSBB tended to decrease the risk of variceal bleeding when compared with the use of NSBB alone (isosorbide‐mononitrate plus NSBB vs NSBB: odds ratio = 0.67, 95% confidence interval 0.40–1.13, P = 0.13; spironolactone plus NSBB vs NSBB: odds ratio = 0.41, 95% confidence interval 0.10–1.69, P = 0.22). Adverse events were more frequently observed in the combined therapy groups. Conclusions Based on the available evidences, no combined therapy can be recommended as the first‐line treatment for the primary prevention of variceal bleeding currently. Further studies with large sample sizes and long‐term follow up are warranted.